The Effects of Digital Transformation In The Covid-19 Era Towards Elements of An Agreement - Imelda Martinelli; Samantha Elizabeth Fitzgerald (Asian Journal of Social and Humanities, 2023)
The development of Indonesia's digital transformation has a high potential for success due to the Indonesian people themselves possessing great interest in adapting to use of digital innovations. In promoting the development of information technology, the government, authorized institutions, companies and all parties involved must be aware of the rapidity with which access is expanded, as well as the accessibility of infrastructure and experts, to prevent disparities in information technology development among regions. Digital transformation is often used to facilitate the process of delivering information and communication between many parties so that the progress of a business, activity or plan can run more quickly. However, there are certain forms of development that can create high-risk legal relationships which generate controversy. Research on these models needs to be further undertaken to avoid contingencies, and the results will be discussed in this scientific paper. The method used in this research is normative based legal research. The research concluded that agreements are carried out after digital transformation is influenced by the subjects involved and related. It is essential for them to agree on how their agreement is made and will be performed as well as its substance. Good faith remains the foundation of the parties' commitment to achieve what they have agreed to. Subjects who act as users must comply with the terms of the agreement in entirety as the initial promisors, both on a practical level and in the "delivery" model, which is perilous for the subject who is the user